Methanol electrochemical refinery towards formate - Meng, Fanxu (Nanyang Technological University, 2023)
Upgrading the fossil-fuel-based chemical production processes with more sustainable and carbon-neutral concepts is beneficial to mitigate the global warming effect and the energy crisis. The innovative electrochemical refinery (e-refinery) technology, which converts chemicals to more value-added products with electricity, is one of the most promising paths to address carbon-neutral manufacturing. Moreover, this concept offers better control of the driving force of the electrocatalytic reactions for selectivity tuning and thus opens up a significant opportunity for optimizing partial reduction or oxidation conversions. As a result, this thesis focuses on methanol e-refinery reaction towards formate. Iron-substituted lanthanum cobaltite perovskites, which have shown excellent performance in other electrocatalytic reactions, such as oxygen evolution reaction (OER), oxygen reduction reaction (ORR), and other small molecule oxidation reactions), are examined for the methanol e-refinery reaction. The experimental and theoretical results show that the Fe/Co ratio in the catalysts greatly influences the activity and selectivity, which is attributed to the relatively high affinity that Fe has to methanol and Co has to hydroxide ions. Because a balanced affinity level to the reactants is favored, when the Fe and Co content is equal, the catalyst presents the highest formate production rate among the five catalysts and a relatively high FE of 44.4%. After that, the lattice participation phenomenon, which has been observed in OER, is validated for the methanol e-refinery reaction. With the oxygen-eighteen-labeled catalysts, gas chromatography-mass spectrometry (GCMS) measurements have revealed that for highly covalent catalysts the lattice oxygen participates in the reaction; however, for less covalent catalysts lattice oxygen is not involved. Moreover, the highly covalent catalysts exhibit higher formate production activity and Faradaic efficiency (FE), and they are roughly proportional to the catalysts' O-2p-band positions. Nickel hydroxide, with the highest O-2p-band center level among the seven studied catalysts, presents a near 100% formate Faradaic efficiency over a wide range of current densities in the MEA tests. In light of those findings, potential methanol e-refinery mechanisms that encompass the participation of lattice oxygen to explain the correlation between the O-2p-band center levels and formate production rate or Faradaic efficiencies of the catalysts are presented. With the above mechanism understanding of the methanol e-refinery reaction, the third project focuses on reducing the large overpotential of methanol e-refinery, which could potentially circumvent the competing side reaction: OER. As illustrated above, though the previous works have proven the viability of methanol e-refinery, the reaction is still operating at high potentials (mostly larger than 1.35 V versus reversible hydrogen electrode), in which OER is a strong side reaction. Yet, the theoretical potential for methanol e-refinery is around zero voltage versus standard hydrogen electrode (SHE). As a result, reducing the overpotential is one of the most crucial obstacles to be resolved for methanol e-refinery. In the third project, with the Pt-decorated nickel hydroxide as the electrocatalyst, the onset potential of methanol e-refinery has been reduced to around 0.6 V versus RHE at 0.8 V versus RHE during the 2-hour chronoamperometry (CA) test. The low operation potential of methanol e-refinery circumvents the competition of OER, which could potentially improve the efficiency of formate production during the reaction. Those findings provide a promising strategy to overcome the sluggish kinetics of methanol e-refinery.